Socio-Economic Conditions in Relation to Seaweed Farmers' Income and Independence - Bakarbessy, Derek (Interdisciplinary Social Studies, 2023)
ground: With the potential of natural resources, seaweed become one of promising commodities which can improve and accelerate national development in general and marine and fishery sector development particularly. Marine and fishery sector development is not only exploitation approach but it is directed toward attempt to improve added value of cultivation. Aim: This study aims to analyze the effect of social economic factor toward income and independence of seaweed farmer in Maluku Tenggara Barat Region. Method: This study was designed with the type of model combination sequential explanatory design. The population in this study was all seaweed farmers in Maluku Tenggara Barat region as 1.485 people. The determination of sample was 10% from total population, so that sample of 148 seaweed farmers. The data was analyzed by using path analysis. Findings: The result of reference study shows that (1) capital is the most affecting variable toward independence of cultivation as 55,6% (2) Land Area was the second affecting variable toward independence as 45,2% ; (3) the number of dependent family member  is the third affecting variable toward independence as 29,9%; (4) interaction education and counseling is the forth affecting variable toward independence as 24.4% ;experiences was the fifth affecting variable toward independence as 24.3%; (6) age is the sixth affecting variable toward independence as 18.5%; (7) counseling intensity is the seventh affecting variable toward independence as 14.1%; (8) education is the eighth affecting variable toward independence as 11.8%.